Relation of Irritable Bowel Syndrome with Some Biochemical Parameters and Emotional Intelligence - Mashhedy*, Lamia (University of Thi-Qar Journal of Science, 2011)
Irritable bowel syndrome (IBS) is a common gastrointestinal condition characterized by abdominal pain and cramps; changes in bowel movements. There is no cure for IBS; however, dietary changes, stress management, and sometimes medications are often able to eliminate or substantially reduce its symptoms. Although the exactcauses of IBS are unknown, research suggests that people with IBS may have a colon that is more sensitive and reactive to certain foods and stress. Stress feeling mentally or emotionally tense, troubled, angry or overwhelmed stimulates colon spasms in people with IBS. Therefore we discuses the relation between IBS and the end product of lipid peroxidation (malondialdehyde) due to oxidative stress and determination of superoxide dismutase and catalase activity as antioxidants